Facile one-pot synthesis of Cu x O/TiO2 photocatalysts by regulating Cu oxidation state for efficient solar H2 production - Rajendran, Sivaraj; Mani, Sunesh S.; Nivedhitha, Thazhath R.; Asoka, Anantha Krishnan; Arun, Pushkaran S.; Mathew, Thomas; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2023)
Development of highly efficient CuxO/TiO2 photocatalysts by regulating the oxidation state of Cu exclusively in either single or mixed oxidation state(s) is desirable but difficult to achieve without employing any external reagents. The present work describes a one-pot synthesis strategy to obtain CuxO/TiO2 photocatalysts with Cu in +1 and/or +2 by using a suitable combination of ethylene diamine tetra acetic acid (EDTA) and ethylene diamine, carefully varying the Cu content, and heat treatment process. CuxO/TiO2 nanocomposite catalysts were characterized thoroughly by physicochemical methods. Textural analysis indicates a high dispersion of CuxO on porous TiO2 with p-n heterojunctions between them in CuxO/TiO2 catalysts. UV-visible spectral analysis suggests the presence of CuxO on TiO2 with significantly extended absorption from the UV to the visible region. X-ray photoelectron spectroscopy (XPS) analysis indicates a strong synergetic interaction between TiO2 and CuxO due to the comparable CB potential and p-n heterojunction at the interface among them. Photoelectrochemical studies demonstrate excellent charge-carrier separation efficiency, low charge-transfer resistance, and high double-layer capacitance with Cu2O/TiO2 photocatalysts. Photocatalytic efficacy of a CuxO/TiO2 nanocomposite in thin-film form has been demonstrated for solar hydrogen generation in sunlight. The incorporation of Cu+ in TiO2 largely improves the H-2 production, and all of the CuxO/TiO2 nanocomposites in thin-film form exhibited higher efficiency compared to their particulate/suspension counterpart. Among the composite catalysts, TiCu-1 in thin-film form, with Cu exclusively in +1 oxidation state, exhibited a high hydrogen production rate of 7.06 mmol/hg, which is 6 times higher than its suspension counterpart; also catalysts containing mixed Cu-oxidation states exhibited about 60-70% activity as that of TiCu-1. The superior performance of Cu2O/TiO2 nanocomposites in thin-film form was due to their enhanced light harvesting ability, high mass transfer rate, and easy accessibility of the reactant species to the active sites.
Keywords: heterojunction; Photocatalysis; Solar hydrogen; thin film; titania